2021
DOI: 10.1080/20430795.2021.1883984
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of strategic and financial variables of corporate sustainability and ESG policies on corporate finance performance

Abstract: Over the past few decades, there has been a sharp increase in interest by investment professionals to become more socially responsible with regards to their decision making relating to their choice of investments and overall make-up of their portfolios. This paper conducts various tests to establish a link between Corporate Social Responsibility (CSR) and Corporate Financial Performance (CFP). This paper adds a strategic management element by establishing various frameworks that corporations can include in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(44 citation statements)
references
References 43 publications
1
25
0
Order By: Relevance
“…The social responsibility can affect the reputation of companies and customer satisfaction, which increases their value during their practice of the social responsibility activities (Landi & Sciarelli, 2018;Gillan et al, 2021;Chen et al, 2021). These results are consistent with some other studies that showed a positive relation between the company's social responsibility and its reputation (Karwowski & Raulinajtys-Grzybek, 2021;Gillan et al, 2021;Weston & Nnadi, 2021). These studies indicated that the increased disclosure of the social responsibility practices increases its market value and profitability (Jordaan et al, 2018;Kuo et al, 2021;Mohammad & Wasiuzzaman, 2021).…”
Section: Second: Strategy Of the Social Performancesupporting
confidence: 88%
“…The social responsibility can affect the reputation of companies and customer satisfaction, which increases their value during their practice of the social responsibility activities (Landi & Sciarelli, 2018;Gillan et al, 2021;Chen et al, 2021). These results are consistent with some other studies that showed a positive relation between the company's social responsibility and its reputation (Karwowski & Raulinajtys-Grzybek, 2021;Gillan et al, 2021;Weston & Nnadi, 2021). These studies indicated that the increased disclosure of the social responsibility practices increases its market value and profitability (Jordaan et al, 2018;Kuo et al, 2021;Mohammad & Wasiuzzaman, 2021).…”
Section: Second: Strategy Of the Social Performancesupporting
confidence: 88%
“…Nevertheless, there are also studies showing negative effects, for instance suggesting that firm investment in SP diverts funds that could be used for productive investment (Smith and Sims, 1985; Peng and Yang, 2014). There are also studies reporting no relationship between SP and FP (Fauzi et al , 2007; Weston and Nnadi, 2021).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%
“…First, we examine how corporate ownership and equity funds are (involuntarily) responsible for investment in the firms that are deemed problematic with the ESG (Environment, Society and Governance) standards. While the literature has recognized that “ESG is being incorporated into other portfolio products, such as ETFs” in the last several years [ 20 ], and the scholarly literature has exclusively addressed the impact of ESG scores on the financial performance of ETFs, corporate profitability, and investment decision-making among others [ 21 , 22 ]. Our analysis differs from the existing studies in that we study the connectivity of corporate ownership and investment funds to non-ESG firms, rather than the impact of ESG standards.…”
Section: Discussionmentioning
confidence: 99%